The Influence of "Pojok Baca" on the Fulfillment of Children's Educational Rights in Turunrejo Village, Kendal District: Legal and Literacy Perspective - Amallia Lathifa Anfasa; Putri Hani; Naely Silvia Najwa; Misrinah; Muhammad Firdaus Setyawan (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
The 'Reading Corner' program in Turunrejo Village, Kendal District, has demonstrated an increase in children's reading interest and literacy skills. Observations and interviews with children and parents reveal that many children who initially rarely read are now more active using the reading corner, with some showing significant improvement in their reading and comprehension abilities. Despite these clear advances, challenges such as budget constraints, a lack of diverse book collections, and insufficient local government support persist. The considerable distance from the city center also affects the regular procurement of new books. Several studies highlight that similar challenges are faced by literacy programs in remote areas. Additional support, training for managers, and enhanced resources are necessary to maximize the benefits of the 'Reading Corner' program for children.